2020
DOI: 10.1080/15685551.2020.1816344
|View full text |Cite
|
Sign up to set email alerts
|

Design and application of polyurea microcapsules containing herbicide (oxyfluorfen)

Abstract: Polyurea, a controlled release material, has been widely applied in agricultural fields due to high thermal stability and low cost. In this article oxyfluorfen polyurea microcapsules suspension was successfully prepared by interfacial polymerization using diisocyanate and polyamines such as Ethylenediamine, Hexamethylenediamine, Diethylenetriamine in presence of green solvent, i.e., N, N-dimethyldecanamide. The microcapsule suspension of oxyfluorfen has not been researched yet by using solvent N,N-dimethyldeca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 21 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…Chinnusamy et al (2012) reported that herbicide application reduced weed seed germination during initial growth stage of crop which minimized nutrient depletion by weeds resulting in superior growth attributes of rice. Li et al (2019) and Rao et al (2020) observed that application of polyurea encapsulated oxyfluorfen showed superior crop growth than commercial products.…”
Section: Introductionmentioning
confidence: 99%
“…Chinnusamy et al (2012) reported that herbicide application reduced weed seed germination during initial growth stage of crop which minimized nutrient depletion by weeds resulting in superior growth attributes of rice. Li et al (2019) and Rao et al (2020) observed that application of polyurea encapsulated oxyfluorfen showed superior crop growth than commercial products.…”
Section: Introductionmentioning
confidence: 99%
“…Инкапсулированный в полимочевину оксифлуорфен был стабилен и нетоксичен для риса (Rao et al, 2020(Rao et al, , 2021. Пендиметалин был успешно инкапсулирован в полиуретанмочевину; состав оболочки существенно влиял на форму микрокапсул и высвобождение ДВ (Yılmaz et al, 2021).…”
Section: современные тенденции в разработке гербицидовunclassified
“…For controlled‐release applications, only some non‐water‐soluble polymers based on, for example, polyesters, polyurea, and polyurethane systems are commercially used, which are all very cost‐efficient but are not considered readily biodegradable in soil 98 . Polyurea systems contain also a high thermal stability 99 and are safe for the environment 100 . Especially the cross‐linking density applied in the microencapsulated systems, which is required to obtain a stable capsule, prevents a readily biodegradation.…”
Section: Water‐soluble and Water‐dispersible Polymers In Crop Protectionmentioning
confidence: 99%